THE THEORY OF GENERATIONS AS A BASIS FOR FORMING THE EFFECTIVE MOTIVATIONAL MECHANISM IN THE ORGANIZATIONAL CULTURE OF THE ENTERPRISE - YANIIEVA, Daria (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper considers the theory of generations as a leading factor in the formation of a motivational mechanism in organizational culture, since any organization tries to unite employees around certain values, principles and guidelines, which can be both common and radically different for individual generations. The purpose of the article is to substantiate the expediency of involving the theory of generations in the formation of a motivational mechanism in the organizational culture of the enterprise. The theory of generations of N. Howe and W. Strauss is considered considering that the age structure of the organization is an important factor for building an effective mechanism of motivation in the organizational culture. The formation stages of the theory of generations are presented, periodization according to four different types of era is presented. Four periods of the cycle of transformations through which each generation passes are characterized, as well as four types of generational archetypes. It is outlined that the cycles of archetypes are repeated from generation to generation, the principle of cyclicity is defined. For the considered five types of generations according to the conventional periodization of 20 - 22 years, a generalized characteristic of each of them is given, in particular in the Ukrainian context, namely with regard to the events that formed the philosophy of life of one or another generation and influenced their activity during their life. Quantitative characteristics of the working population of Ukraine were determined on the basis of statistical data. The number of the working population of Ukraine belonging to different age groups has been determined. The specified factors affecting the quantitative composition of employees belonging to different age groups are presented. Along with generations X and Y, the youngest age new generation, which has only partially started working and whose share in the labor market will increase every year, is examined in detail. The tools for ensuring the effectiveness of the work of new generation are defined. In addition, it is stated that various theories of motivation should be used to form an effective motivation mechanism in the organization, with the obligatory consideration of the theory of generations for further practical application.